Effect of sonochemical duration on the synthesis of vanadium oxide nanowires - S.Suhaizam; Y.H. Taufiq Yap; Wong Yee Ching (2012)
Nanowires V2O5 was synthesized by sonochemical pretreatment using NaNO3 in several durations (30 – 120 min). XRD patterns of the sonicated V2O5 gave similar structure with a pure V2O5 phase without the presence of other diffraction peaks which attributed to any different phases. Prolonged the duration of sonication also has led to an increased in the intensity peaks of the diffraction peaks, which indicate relatively high crystallinity. TEM micrographs show that after 120 min pretreatment, nanowires V2O5 with much smaller diameter (~10 – 15 nm) was produced and has explained the main factor for the decrement in the crystallite sizes of the sonicated V2O5 found in the XRD data. The TEM micrographs also show that the sonicated V2O5 formed bulk of nanowires V2O5 when the duration of sonication was prolonged. The high energy of ultrasonic pretreatment induced the self-assembled phenomenon which caused the nanowires V2O5 to agglomerate and formed bundle.